(untitled) (Impetus, 2021)
In every formative process, the constitution of a subject is mediated by the interaction, mainly, between two actors; the so called apprentice, subject to be educated and transformed, and the teacher, mediator subject in the education- transformation process. In the Physical Education Faculty of the National Pedagogic University (FEF-UPN, in Spanish), inquiring about this interaction is a priority due to its challenge: to educate educators, a crucial point to its suitability. Accounting for the processes that occur in this interaction, learning and teaching, implies to carry out an auto-evaluation with comprehensive and explicative purposes in order to influence, in a proactive and critical way, the ideal curricular development in the process of educating teacher subjects, and for that purpose it is necessary to investigate the metacognitive processes about the teacher’s and the apprentice’s knowledge. According to this, this research work accounts for the learning styles and, as an appreciatory guideline of their suitability, relates them to the academic achievement. The research is descriptive-exploratory, it collects and identifies a general background, from a characterization and a statistical correlation in an initial level, and it aims at proposing an investigative field in the context of curricular evaluation, in general, and its didactic component for teachers’ education, in particular. The methodology contrasts the results of the CHAEA questionnaire, proposed by Honey & Alonso (1994), in order to identify learning styles, with academic achievement expressed in cumulative average, with a census sample from the bachelor’s degree program in physical education.